2004
DOI: 10.1111/j.1475-6773.2004.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication Prescriptions among Elderly Nursing Home Residents: Their Scope and Associated Resident and Facility Characteristics

Abstract: Objective. To estimate the scope of potentially inappropriate medication prescriptions (PIRx) among elderly residents in U.S. nursing homes (NHs), and to examine associated resident and facility characteristics. Data Sources. The 1996 Medical Expenditure Panel Survey Nursing Home Component (MEPS NHC), a survey of a nationally representative sample of NHs and residents. Study Design. The PIRx, defined by Beers's consensus criteria (1991, 1997), was identified using up to a year's worth of NH prescribed medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
88
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 29 publications
11
88
1
4
Order By: Relevance
“…In a study of 211 Medicare enrollees, Rask et al (2005) found that PIMs were not associated with DRP; indeed, the majority of DRPs in this study occurred in persons prescribed non-PIMs. Researchers in several recent controlled studies, however, have begun to show a link with the Beers criteria and poorer patient outcomes (Klarin, Wimo, & Fastbom, 2005;Lau et al, 2004). Lau et al found PIM use was associated with increased risk of hospitalization and increased risk of deaths among NH residents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 211 Medicare enrollees, Rask et al (2005) found that PIMs were not associated with DRP; indeed, the majority of DRPs in this study occurred in persons prescribed non-PIMs. Researchers in several recent controlled studies, however, have begun to show a link with the Beers criteria and poorer patient outcomes (Klarin, Wimo, & Fastbom, 2005;Lau et al, 2004). Lau et al found PIM use was associated with increased risk of hospitalization and increased risk of deaths among NH residents.…”
Section: Discussionmentioning
confidence: 99%
“…PIMs are medications identified through expert panel review as having risks that outweigh benefits (Beers et al, 1991). Since the early 1990s, the prevalence of PIMs has been examined in a (Lau, Kasper, Potter, & Lyles, 2004), outpatient (Aparasu & Sitzman, 1999Curtis et al, 2004), acute care (Onder et al, 2005), and community settings (Zhan et al, 2001). For research purposes, use of explicit criteria is generally preferred over the use of implicit criteria applied by expert reviewers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expert consensus panels have defined potentially inappropriate medications (PIMs) as medications that generally should be avoided among patients 65 years or older either because they are ineffective or because associated adverse effects outweigh potential benefits and a safer alternative exists. 3,4 Recent studies examining the prevalence of PIM use in various medical settings in the US have found that at least one PIM was prescribed in 8-13% of ambulatory visits, 5,6 50% of nursing home residents, 7 and 17% of emergency department visits. 8 PIM use among elderly home health patients in the US remains unknown.…”
mentioning
confidence: 99%
“…[2][3][4] En España, las personas mayores de 65 años representan el 17 % de la población total, mientras que el gasto generado en su atención representa el 50 % del total y alrededor del 70 % de la factura farmacéutica (Fuente: Instituto Nacional de Estadística).Diversos artículos consultados, sobre el uso de medicamentos dedicados a la atención de las personas mayores, estudian el abordaje de fármacos específicos en determinadas enfermedades crónicas o en su consumo inapropiado, pero la mayoría, son coincidentes en demostrar perfiles de sobre-utilización, que ocasionan un mayor riesgo en desarrollar efectos adversos, interacciones medicamentosas y errores en la medicación. [5][6][7][8][9] Por tanto, a todos los actores sanitarios se les plantea la necesidad de reducir el consumo injustificado de fármacos, optimizar su eficiencia y promover estrategias orientadas a facilitar el uso racional del medicamento, con criterios de seguridad y eficacia. [10][11][12][13][14][15][16] Desde el Servicio Catalán de la Salud (CatSalut), análogo a otras comunidades autonómicas, se están realizando diversas estrategias que intentan abordar este problema de actuación, tanto en los centros residenciales geriátricos como en sus entidades proveedoras de referencia.…”
Section: Introductionunclassified